Exosomal tumor necrosis factor‐α from hepatocellular cancer cells (Huh‐7) promote osteoclast differentiation - Li, Ching‐Hao; Palanisamy, Kalaiselvi; Li, Xin; Yu, Shao‐Hua; Wang, I‐Kuan; Li, Chi‐Yuan; Sun, Kuo‐Ting (Journal of cellular biochemistry, 2021)
Bone is the common extra‐hepatic site for cancer metastasis. Hepatic cancer is associated with a higher incidence of pathological fracture. However, this important regulatory mechanism remains unexplored. Thus, exosome‐mediated cell‐cell communication between hepatocellular cancer and bone might be key to osteolytic bone destruction. Huh‐7 exosomes were characterized for size and exosome marker expressions (CD63, Alix). Exosome mediated osteoclast differentiation in the RAW 264.7 cells was monitored from day 1 to 6 and multinucleated osteoclast formation and bone resorption activity were analyzed. The osteoclastogenic factor expressions in the exosomes and osteoclast differentiation markers such as tumor necrosis factor receptor 6 (TRAF6), nuclear factor κB (NF‐κB), nuclear factor of activated T‐cells, cytoplasmic 1 (NFATc1), and cathepsin K (CTSK) were analyzed using western blot. Exosomes released by liver cancer cells (Huh‐7) promoted osteoclast differentiation in RAW 264.7 cells. Analysis of osteoclastogenic factors in the exosomes showed that exosomes were specifically enriched with tumor necrosis factor α (TNF‐α). Huh‐7 exosomes promoted osteoclast differentiation by significantly increasing the number of TRAP‐positive multi nucleated osteoclasts and resorption pits. Importantly, exosomes upregulated osteoclast markers TRAF6, NF‐κB, and CTSK expressions. Further, neutralizing exosomal TNF‐α reverted exosome‐mediated osteoclast differentiation in RAW 264.7 cells. Collectively, our findings show that cellular communication of exosomal TNF‐α from hepatocellular cancer cells (Huh‐7) regulates osteoclast differentiation through NF‐κB/CTSK/TRAP expressions. Thus, exosomal TNF‐α might act as an important therapeutic target to prevent hepatocellular cancer mediated pathological bone disease.